Saberes e práticas socioambientais na pesca artesanal do caranguejo-uçá na Amazônia Bragantina (Pontinha do Bacuriteua-PA) - OLIVEIRA, Marcelo do Vale (Universidade Federal do Pará, 2021)
Our objective was to bright the knowledge related the socio-environmental practices of the crab pickers of the Pontinha de Bacuriteua community in Bragança-PA. To understand the way of life, an interdiplinary qualitative approach on artisanal fishing and fishing communities was necessary, encompassing areas of knowledge such as antropology, sociology and history. The applied methodology was composed of semi-structured interviews, aided by direct observation. The main results were the identification that the knowledge of the biological cycles of the crab, the movements of the tides, the phases of the moon, the physical-chemical composition of soil are the essential instruments in the capture of the crustacean in focus. Such are composed of a set of knowledge that the gunners learned with and for previous generations and which are put into practice when moving around their workplaces, daily